Update on coronary artery spasm 2022 – A narrative review. (15th July 2022) - Seitz, Andreas; Martínez Pereyra, Valeria; Sechtem, Udo; Ong, Peter
Abstract: Importance: In today's era of precision medicine a renaissance of functional coronary disease including coronary artery spasm (CAS) can be observed. This development is fueled by novel diagnostic methods as well as first evidence from randomized trials regarding targeted treatment approaches. The present review provides a contemporary update on advances in the pathophysiological understanding, diagnosis, treatment and prognosis of CAS. Observations: A MEDLINE/PubMed search within the period from 2010 to 2021 was performed focusing on original articles, randomized clinical trials, meta-analyses and systematic reviews on CAS. Among 1.639 citations, articles that were considered to contain the most important and novel data on CAS were included in this narrative review. These articles comprise reports on new insights into the complex pathophysiology of CAS, state-of-the-art invasive diagnostic procedures, reports on diagnosis of microvascular spasm and diagnosis of CAS in special conditions such as MINOCA, post-PCI angina or myocarditis. Moreover, novel treatment approaches are included such as nebivolol, endothelin-1-receptor antagonists and soluble guanylate cyclase stimulators. Furthermore, recent follow-up studies have provided new data on long-term prognosis of affected patients. Conclusions: Scientific progress during the last decade has led to a better understanding of CAS. Today, standardized international diagnostic criteria are available and promising randomized treatment trials are on their way. Moreover, there has been increasing evidence regarding the prognostic value of CAS testing. However, despite many advances, CAS remains a complex and not fully understood condition and more research is needed to better characterize and treat affected patients. Highlights: Epicardial and microvascular coronary spasm are frequent mechanisms of angina. Endothelial dysfunction and VSMC hyperreactivity are responsible for coronary spasm. Coronary spasm is associated with increased morbidity but not mortality. Trials investigating targeted medical treatment of coronary spasm are underway.